2005
DOI: 10.1080/17441690500211114
|View full text |Cite
|
Sign up to set email alerts
|

Writing therapy in brief workplace counselling: Collaborative writing as inquiry

Abstract: The purpose of this collaborative research was to reflect on one client's experience of using writing therapy during brief workplace counselling. The client/co‐researcher used expressive and creative writing between counselling sessions, the benefits of which are reported. A brief review of the literature on writing therapy is provided. The focus of the study is on investigating the process of writing therapy from the client's point of view. The epistemological assumptions and research methods are influenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…Previous qualitative research with depressed primary care patients,34 hospice patients7 and counselling clients35 – 38 gave similar results to this study. Research with women with breast cancer indicated positive effects 39 40.…”
Section: Previous Researchsupporting
confidence: 85%
“…Previous qualitative research with depressed primary care patients,34 hospice patients7 and counselling clients35 – 38 gave similar results to this study. Research with women with breast cancer indicated positive effects 39 40.…”
Section: Previous Researchsupporting
confidence: 85%
“…A serendipity experience was the bonus, perhaps also therapeutic, effect individual/group writing had on us (Lepore & Smythe, ; Wright, ):
Writing personal stories can be therapeutic for authors as we write to make sense of ourselves and our experiences, purge our burdens and question canonical stories—conventional, authoritative and "projective" storylines that "plot" how "ideal social selves" should live. In so doing, we seek to improve and better understand our relationships, reduce prejudice, encourage personal responsibility and agency, raise consciousness and promote cultural change and give people a voice that, before writing, they may not have felt they had.
…”
Section: Methods and Aim Of Studymentioning
confidence: 99%
“…Dessa forma, no que se refere aos campos disciplinares/profissionais, as cartas terapêuticas são utilizadas na terapia familiar (Vidgen & Williams, 2001), na terapia em grupo (Chen, Noosbond & Bruce, 1998), no aconselhamento (Paré & Rombach, 2003) e na prática da equipe de enfermagem (Erlingsson, 2009). Os diferentes contextos de uso incluem desde a clínica psicoterápica em geral (Pyle, 2009) e as consultas psiquiátricas (Couper & Harari, 2004), passando pelas escolas com os adolescentes, pais e professores (Oliver, Nelson, Cade & Cueva, 2007), até o aconselhamento breve nas empresas (Wright, 2005). As cartas terapêuticas também foram utilizadas de maneira efetiva com diferentes populações, seja com pessoas que sofrem distúrbios alimentares (Davidson & Birmingham, 2001), com experiências traumáticas passadas (Esterling, L'Abate, Murray & Pennebaker, 1999), com adolescentes e suas famílias (Goldberg, 2000) e com pacientes em crise (Tubman, Montgomery & Wagner, 2001).…”
Section: As Cartas Terapêuticas Na Prática Clínica: De Para E Entre unclassified